Healthcare utilization and knee osteoarthritis symptoms among urban older Malaysian - Kamsan, Siti Salwana; Singh, Devinder Kaur Ajit; Tan, Maw Pin; Kumar, Saravana (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Knee osteoarthritis (OA) is a prevalent chronic disorder in the older population. While timely management is important to minimize the consequences of knee OA, information on the utilization of healthcare services among this population remains limited. Therefore, the objectives of this study were to determine the healthcare utilization and its associated factors in older persons with knee OA. Cross-sectional data from 1073 participants aged 60 years and above from the Malaysian Elders Longitudinal Research (MELoR) study were included. The utilization rate of healthcare services was quantified. Factors related to the utilization of healthcare services were determined using logistic regression analysis. Healthcare utilization among participants with knee OA was significantly higher than those without knee OA (p < 0.01). Outpatient usage was higher (p < 0.01) in comparison to inpatient and pharmacotherapy. Being married and having an income were significantly associated with seeking outpatient care (OR: 11.136, 95% CI: 1.73–52.82, p < 0.01) and pharmacotherapy (OR: 10.439, 95% CI: 1.187–91.812, p < 0.05), while females were less likely to utilize inpatient care services (OR: 0.126, 95% CI: 0.021–0.746, p < 0.05). The higher rate of healthcare utilization among older persons with knee OA indicates the increased healthcare needs of this population, who are commonly assumed to suffer from a benign disease.